Research on a connotation and assessment index system of eco-communities. Issue 6 (2nd November 2017) - Feng, Qiyuan; Liu, Xin; Tang, Lina; Shi, Longyu; Jiang, Jiaying; Su, Xiaodan
ABSTRACT: Eco-communities integrate construction and management with a comprehensive view of the environment and can be reflected through the aspects of 'harmony, ' 'comfort, ' 'conservation, ' and 'intelligence.' In this study, relevant assessment indices were sorted and summarized to develop an eco-community evaluation system (ECES) based on basic principles of science, management, and operation. ECES assesses communities based on four parameters: outdoor environment, indoor environment, resource consumption, and operation and management. The main goal of ECES is to guide the sustainable development of eco-communities.